Deposition and early diagenesis of microbial mud in the Florida Everglades. Issue 6 (20th March 2019) - Pederson, Chelsea L.; Klaus, James S.; Swart, Peter K.; Mcneill, Donald F.
Abstract: Microbial carbonate mud in the modern (<4 kyr) palustrine environment of the Florida Everglades is surprisingly susceptible to early diagenetic alteration. The low‐Mg calcite crystals show an open, trellis‐like crystal structure that yields a high surface area to volume ratio. This textural complexity, likely to be a result of organic influence, leads to abundant reaction sites vulnerable to both dissolution and subsequent precipitation. Rapid degradation of organics is attributed to both aerobic and anaerobic metabolisms. Geochemical signatures suggest increased denitrification within the freshwater environment and increased sulphate reduction at the (slightly) brackish mangrove transition zone. A transition from a freshwater to brackish depositional environment is likely to follow the Holocene sea‐level transgression. The textural complexity in these microbial carbonates causes an unexpectedly low preservation potential of original textural and geochemical signatures, even in low‐Mg calcite. Given the potential for early diagenesis of palustrine and perhaps other microbial carbonates, they should be used cautiously as archives for palaeoenvironmental proxies.